Diabetes Self-Management Education in South Auckland, New Zealand, 2007-2008 - Silva, Martha (Centers for Disease Control and Prevention, 2011)
INTRODUCTION: Self-management education programs seek to help patients realize that they are their own principal caregivers and that health care professionals are consultants who support them in this role. The aim of this study was to evaluate a diabetes self-management education program implemented as part of a district-wide approach in South Auckland, New Zealand, which has some of the highest prevalence rates for diabetes and is one of the most ethnically diverse and deprived regions of New Zealand. METHODS: Self-management attitudes and behaviors were monitored with the use of questionnaires before and after program implementation. Clinical outcomes such as hemoglobin A1c, body mass index, and blood pressure were also tracked before the program began and 3 months after the program ended. Participant focus groups and facilitator interviews were conducted to explore perceptions of the program. RESULTS: Participants showed improvement in attitudes toward their own ability to manage their diabetes; in diet, physical activity, and foot care; and in hemoglobin A1c levels 3 months after the end of participation. Participants also reduced their sense of isolation when dealing with their diabetes. However, catering to the needs of a multiethnic community is extremely resource-intensive because of the need to provide adequate language and cultural interpretation. CONCLUSION: Self-management education can work in multiethnic, high-needs communities in New Zealand. Programs must ensure they enable the appropriate mechanisms and have appropriate resources to support the community's needs.